The postwar African American novel : protest and discontent, 1945-1950 - Brown, Stephanie, 1970- (Jackson : University Press of Mississippi, 2011)
Americans in the World War II era bought the novels of African American writers in unprecedented numbers. However, the names on the books were less well-known ones such as Frank Yerby, Chester Himes, William Gardner Smith, and J. Saunders Redding. This book recovers the work of these innovative novelists, overturning conventional wisdom about the writers of the period and the trajectory of African American literary history. The book also questions the assumptions about the relations between race and genre that have obscured the importance of these once-influential creators.
Introduction -- Beyond protest: retracing the margins of the postwar African American novel -- "If I can only get it funny!": Chester Himes's parodic protest novels -- Frank Yerby and the "costume drama" of Southern historiography -- William Gardner Smith and the cosmopolitan war novel -- J. Saunders Redding and the African American campus novel.
Includes bibliographical references (pages 173-186) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Nervo, Amado; Universidad Sergio Arboleda; American fiction -- African American authors -- History and criticism; American fiction -- 20th century -- History and criticism; Protest literature, American -- History and criticism; African Americans in literature; Discontent in literature; Roman américain -- Auteurs noirs américains -- Histoire et critique; Roman américain -- 20e siècle -- Histoire et critique; Littérature contestataire américaine -- Histoire et critique; Noirs américains dans la littérature.; Mécontentement dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- American -- African American; African Americans in literature; American fiction; American fiction -- African American authors; Discontent in literature; Protest literature, American; Schwarze; Protest; Unzufriedenheit; Roman; Amerikanisch; Motiv; Protest; Schwarze; USA; 1900-1999; Criticism, interpretation, etc